If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18-8z=-10z
We move all terms to the left:
-18-8z-(-10z)=0
We get rid of parentheses
-8z+10z-18=0
We add all the numbers together, and all the variables
2z-18=0
We move all terms containing z to the left, all other terms to the right
2z=18
z=18/2
z=9
| h÷6=-7 | | w4=10 | | h=-(2)^{2}+12(2)+10 | | −7a−10=2−−3a | | -14t-13=-13t+6 | | 100-10n=15n | | 2x+2=9x+0 | | 2xx+4=4x-2 | | h=-(1)^2+12(1)+10 | | 18−5x=x+4 | | 9.54+10.5h=-5.4h | | x=24x5/4 | | -13-3d=-8 | | 2/5(6y-4)+8=10 | | -13-5w-13=-5+2w | | 2x+4x-20=88 | | 2(2.5y+13)-5y=180 | | 15+71x=7 | | 35=7-4x | | 4x-14x+3x=16 | | m/4+10=46 | | (1/2)(7a+1)=18 | | (x+20)=168 | | -8g+9+15g=4g-9 | | 3x(5)=x-8 | | 7+15x=71 | | 25b+5=3b+27 | | y+13/49=40 | | -1=-4-5x | | -3x7=-11 | | 2.2q-17.41+8.6q=15.22-14.3q | | 21x+42=44 |